Analisis Lingkungan Kerja Berdasarkan Tingkat Kebisingan Mesin di PT. Grahadura Leidong Prima - Jenny Maruli Tambun; M. Fazri Pasaribu; Abdul Azis Syarif (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
The production process at PT. Grahadura Leidong Prima uses production equipment that has the potential to cause noise. Officers who operate the equipment are environmental components that are directly affected by the increase in noise. It is alleged that many company employees experience hearing loss when working in these units. This study aims to evaluate the noise in the work unit and determine the effect of noise felt by employees. The research was conducted by directly measuring noise sources for 3 shifts using a sound level meter. Measurements were made at a distance of about 1 m from the noise source at various positions and carried out manually every 5 minutes with an interval of 5 seconds, at maximum operating capacity. In addition, observations were also carried out on employees related to the impact felt while in the factory environment, as well as analyzing medical record data for employees who had worked in the unit. The results of data processing indicate that the machine has a noise level that exposes employees during working hours to exceeding the threshold value, where the noise level is 89.7 dB at the Sterilizer station, 89.6 dB at the Thresser station, while the highest noise level is at Press station 92.3 dB. With noise levels that exceed the threshold value, noise control is carried out using personal protective equipment (PPE) for each employee.